The Effect of Job Satisfaction and Work Motivation on Employee Productivity CV. Yahyo Bengkulu Province - Rahmat Zulfi; Meiffa Herfianti (PT. MEMIKATTA PUBLISHER INDONESIA, 2024)
This study aims to determine the effect of job satisfaction and work motivation on the work productivity of employees of CV Yahyo Bengkulu Province. Respondents of this study were employees who worked at CV Yahyo Bengkulu Province totalling 50 employees. The sampling technique used in this study was total sampling. The results of this study indicate that employee work productivity is influenced by job satisfaction and work motivation with the results of the multiple linear regression equation Y = 2.787 + 0.421X1 + 0.429X2 and the effect is seen from the coefficient of determination or Adjusted R Square (R2) = 0.447 which is 44.7% while the rest is seen from the coefficient of determination. 447 which is 44.7% while the remaining 55.3% is influenced by other variables outside the study.Furthermore, job satisfaction and work motivation simultaneously or together have a significant effect on the work productivity of CV employees. Yahyo Bengkulu Province with a probability value (sig) of 0.000 <0.05. Also, job satisfaction and work motivation partially or individually affect the work productivity of CV employees. Yahyo Bengkulu Province with a probability value (sig) each variable job satisfaction (X1) with a probability value (sig) 0.002 <0.050 has a significant effect on employee work productivity. And Work Motivation (X2) with a probability value (sig) 0.001 <0.05 has a significant effect on employee work productivity.